An exploration of Emotional Intelligence (EI) among technical students in relation to the Malaysian University English Test (MUET) performance, programme and gender - Hamdzah, Nor Lailatul Azilah; Khoo, Linda Mei Sui; Abd Halim, Noor Baiduri; Hanafi, Zulkifli; Suhaimi, Nurdiyana; Hassan, Ruslan (ResearchTrentz Academy Publishing Education Services, 2022)
Previous research has established that emotional intelligence (EI), or the capacity to rationalise one's emotions, is critical in higher education, particularly in the teaching and learning of English. The study's objectives are to examine the relationship between EI and MUET performance among undergraduate students at a technical university and ii) the significant difference of EI levels among 240 respondents from engineering and business course based on their gender and programmes. The data collection method used was a cross-sectional survey with 240 respondents. The respondents were given the EQI questionnaire, which was developed to assess the respondents' EI levels. The findings indicate that EI has a significant correlation with the students' Malaysian University English Test (MUET) performance. Additionally, the findings indicate that there is a significant difference between the gender, the students' course and their EI level, implying that EI has a strong influence on education. As EI plays a significant role in determining students' English language performance, this study suggests that EI skills should be integrated into the English course. Additionally, it is recommended that future research examine the relationship between EI traits and other language abilities such as listening, speaking, reading, and writing.